Optimalisasi Pertumbuhan dan Hasil Pada Tanaman Kedelai Edamame (Glycin max (L) Merill) Melalui Pengaturan Populasi Tanaman - Jumiatun, Jumiatun; Sugiantoro, Wisnu; Galushasti, Andarula; Bambang Irawan, Triono; Puspa Arisandi, Dewi (Agrosains : Jurnal Penelitian Agronomi, 2025)
Edamame soybean plants are large-seeded soybean plants and are harvested fresh. The demand for edamame soybeans continues to increase along with export market prospects and the interest of the Indonesian people. The purpose of this study was to determine the efficiency of planting distance and the ideal number of seeds per hole for the growth and yield of edamame soybeans. This research activity was carried out from November 2022 to January 2023 in Baratan Village, Patrang District, Jember Regency. The research design was a factorial randomized block design (RCBD). Planting distance treatment was the first factor consisting of 20 cm x 15 cm, 25 cm x 20 cm, 20 cm x 10 cm x 40 cm, and 15 cm x 15 cm x 30 cm. While the number of seeds per hole was the second factor consisting of 1 seed per hole and 2 seeds per hole. The results showed that the optimal planting distance was 20 cm x 15 cm because it produced a maximum pod weight per sample or 73.5 g/plant. The treatment of the number of seeds per hole had no significant effect on all treatments.